Virological Investigation of Avian Influenza Virus on Postglacial Species of Phasianidae and Tetraonidae in the Italian Alps. (17th September 2013) - Delogu, Mauro; Ghetti, Giulia; Gugiatti, Alessandro; Cotti, Claudia; Piredda, Isabella; Frasnelli, Matteo; De Marco, Maria A.
Abstract : Land-based birds, belonging to Galliformes order are considered to be potential intermediaries in the emergence of new strains of influenza A viruses (AIVs), but the viral circulation in these birds remains largely unknown. To gain insights into the circulation of AIV in the wild Galliformes populations in Italian Alps, we conducted a virological survey on rock partridge ( Alectoris graeca saxatilis ) belonging to Phasianidae family and on tetraonids including rock ptarmigan ( Lagopus mutus helveticus ) and black grouse ( Tetrao tetrix tetrix ). In 2003 and 2004, during the hunting seasons, 79 wild Galliformes, categorised into age and sex classes, were hunted in the Sondrio Province (Central Alps). Cloacal swabs were collected from 11 rock partridges and from 68 tetraonids including 23 alpine rock ptarmigans and 45 black grouses. We tested cloacal swabs by a high sensitive reverse transcription- (RT-) PCR detecting the matrix gene of AIV. No AIV was detected in the investigated samples, thus, suggesting the lack of AIV circulation in these relict populations in the study period. In terms of threatened species conservation, during wildlife management activities, it is very important to exclude the introduction of AIV-carrier birds in shared territories, a fact representing a health risk for these populations.